Local tourism experiences at World Heritage rice terrace sites in China: A comparative study of Hani Terraces and Longji Terraces - Zhen Yang; Ming Liu; Longyi Cai (PLoS ONE, 2026)
Rice terraces, as quintessential cultural landscapes shaped by long-term human-land interactions, embody productive, ecological, and cultural value while evolving into significant rural tourism destinations. This study examines two World Heritage–listed sites in China—Hani Terraces in Yunnan Province and Longji Terraces in Guangxi Province—using 4,018 visitor reviews collected from the Ctrip platform. Word frequency analysis was conducted to identify recurrent terms in visitor comments and to determine key dimensions of tourism experience. Semantic co-occurrence network analysis was then applied to explore structural relationships among core terms and to reveal differences in visitor perceptions. In addition, chi-square tests were used to identify statistically significant differences in evaluation characteristics and to examine patterns of negative feedback. The results show that Longji Terraces benefit from higher tourism visibility and a larger volume of online reviews, whereas visitors to Hani Terraces place greater emphasis on cultural and heritage values. In contrast, visitors to Longji Terraces tend to focus more on leisure-oriented tourism services. Negative feedback for both sites primarily centers on transportation and management issues. Weather conditions significantly impacted sightseeing at Hani Terraces, while Longji Terraces faced complaints mainly related to service quality. Overall, this study highlights the heterogeneity of tourism experiences across terraced heritage landscapes and identifies key factors shaping visitor perceptions. By extending the application of user-generated content (UGC) in agricultural heritage tourism research, the findings provide empirical evidence to support tourism management, landscape conservation, and the sustainable development of agricultural heritage sites.